Systematic Review (2010-2017) of Evaluation Instruments and Rehabilitation Programs of Social Cognition, Used with People with Schizophrenia [Revisión Sistemática (2010-2017) de Los Instrumentos de Evaluación y Programas de Rehabilitación de la Cognición Social Utilizados Con Personas Con Esquizofrenia] - Loubat-Oyarce, M (Sociedad Chilena de Psicologia Clinica, 2019)
Research is done regarding evaluation instruments and training programs of social cognition in benefit of the rehabilitation processes of patients with schizophrenia.The PRiSM methodology is used, reviewing the Scopus, ISI and ApaPsycNet journals databases, between 2010 and 2017, considering as inclusion criteria pieces of research where instruments with evaluative purposes and rehabilitation programs of the different sub-domains of social cognition for people with schizophrenia are used. 290 articles are found, and 195 which are thoroughly examined, are selected. A summary of 37 instruments is established, and 10 rehabilitation programs of social cognition are described.It is concluded that it is necessary to explicitly state in the literature the properties, reliability and validity of the tests used, so as to measure what is intended to be measured. Also, it is important to describe the programs used in benefit of the social cognition rehabilitation of the patient with schizophrenia. © 2019 by Sociedad Chilena de Psicología Clínica.